Improving the texture and rheology of set and stirred kombucha fermented milk beverages by addition of transglutaminase - Iličić, Mirela, inženjerka tehnologije (Array, 2021)
The possibilities of manufacturing fermented milk beverages by applying kombucha inoculum concentrated by evaporation and with addition of transglutaminase have been investigated. The main aims of this study were to investigate influence of concentrated kombucha inoculum and the addition of transglutaminase (TG) on textural, rheological and sensory properties of set and stirred fermented milk beverages. The results showed that the addition of transglutaminase had a great influence on textural characteristics and rheological properties of kombucha fermented milk beverages. Firmness and consistency of kombucha fermented milk products were significantly increased with the incorporation of TG compared to the control sample. Set samples with TG addition had approximately 90 % higher hysteresis loop area compared to stirred samples, while hysteresis loop area of stirred samples without TG was 60 % lower compared to set samples. The enzymatic treatment of milk with TG improved texture, rheology and sensorial characteristics of set and stirred fermented milk beverages obtained by concentrated kombucha inoculum.